Anterior Knee Pain after Intramedullary Nailing of Tibial Fractures: Medial Parapatellar versus Transtendinous Approach - Kekeç, Ahmet Fevzi; Bozgeyik, Bilgin (European Journal of Therapeutics, 2023)
Objective: Chronic anterior knee pain has been considered as the most frequent postoperative complication of tibial nailing surgery technique. Surgical approaches used for tibial intramedullary nailing include medial parapatellar, transtendinous, and lateral parapatellar techniques, but lateral parapatellar approach is less preferred. The aim of the present study was to determine the role of medial parapatellar and transtendinous approaches on anterior knee pain of patients with tibial diaphyseal fractures treated with intramedullary nail. Methods: A total of 132 patients who were admitted to our emergency clinic with tibial shaft fracture between January 2015 and January 2017 were evaluated retrospectively. Of the 132 patients, 45 patients who were treated with intramedullary nail were included in the present study. Medial parapatellar approach was used in 20 fractures, and transtendinous approach was used in 27 fractures. Results: The mean follow-up period of the patients was 12 (6–15) months. The mean union time of fractures was 5 (3–15) months. Severity of anterior knee pain was assessed by Visual Analog Scale (VAS). There was no statistically significant difference between the medial parapatellar method and the transtendinous method according to proximal nail entry exposures in anterior knee pain (p=0.927). Conclusion: In conclusion, although tibial nailing is a highly successful procedure for fracture healing, anterior knee pain remains the main disadvantage of it. Although our data showed no differences between the groups, the groups were relatively small to accept this null hypothesis with full confidence.